Effect of Force 6® Poultry on Infectious Bursal disease Virus in Vitro: Amjed H. Ulaiwi1, Shony M. Odishio2 and Salah M. Hassan3 - . Ulaiwi, Amjed H. (The Iraqi Journal of Veterinary Medicine, 2015)
The aim of this study was to investigate the effect of force 6 poultry (conc.) in Log. of infectious bursal disease Virus on tissue culture and Virus, on Virus alone and on tissue culture alone. Different concentrations (0.5, 12.5, 25 and 50 µg/ml) were used to consider the anti-viral activity. The result showed effect of force 6® poultry (conc.) in Log. of Infectious Bursal Disease Virus. On tissue culture and Virus, the results revealed higher value with more significant (P˂0.05) differences at concentration (0.5 µg/ml) than other concentrations and control; On Virus alone, it showed more significant (P˂0.05) differences at concentration (0.5 µg/ml) than concentration (50 µg/ml) which showed less value of Virus growth. And on tissue culture alone (chicken embryo fibroblast) it showed lesser value and significant (P˂0.05) differences than other concentrations. In conclusion, the main changes in tissue culture explained at concentration (0.5, 25 and 50 µg/ml) but not (12.5 µg/ml and control). This group also were more affected on Virus titer when compared with other than two groups (tissue culture and Virus and Virus alone).